THE ROLE OF FISCAL POLICY IN BUILDING DEMOCRACY AND OVERCOMING ECONOMIC RECESSION IN INDONESIA - Muhammad Istan (LPPM STIE Muhammadiah Bandung, 2022)
The state, as an entity, has the authority to obtain income from taxes from its citizens. However, to develop, there is a need for financial management in the tax arrangements received. This tax regulation is a fiscal policy that can be useful in overcoming the economic recession in Indonesia. This study aims to see how fiscal policy can affect the development of democracy and overcome the economic recession that has occurred in Indonesia. The method used in this research is a qualitative approach. The data used in this research comes from the results of previous research or studies that still have relevance to this research. This study found that fiscal policy can help build democracy in Indonesia by opening employment opportunities, increasing national income and investment, and increasing economic stability. As for overcoming an economic recession, fiscal policy can help achieve existing development targets and boost economic growth.